Fluxos globais no século XVIII: a produção do modus vivendi e operandi no entorno da Estrada Real Picada de Goiás - Ana Maria Nogueira Rezende (2017)
This study was guided by the search for different process of historical, geographical, economical and cultural order, that have influenced the construction of the Brazilian space, and, consequently, Minas Gerais. The Brazilian colonial period was a booming time in the formation/construction of new spaces, many of which lead to contemporary cities.Therefore, a number of studies focus on the modus vivendi and operandi that gave birth to several colonial cities/regions in Brazil. This paper tries to understand how was the development of the region of Picada de Goiás, a royal road authorized in the 18th century. It will also explore the way assets and commodities flux carries important informations about the base of the culture at this time and region. More specifically, it aims to understand how was the formation of the local culture, through the analysis of global fluxes and its contribution to the constitution of the local identity and the cultural landscape around Picada de Goiás. Using as analysis support the Appadurei's (2004) theory, it emphasizes overlay of 5 fluxes: people, ideas, technology, money, images and ideals (so called Etnoscapes, Technoscapes, Finalcial scapes, Mediascapes and Ideascapes). The analysis of the chatacteristics of the fluxes that create the region of Picada de Goiás leads to a proposal to adapt Mediascapes and substitute them for "Information Scapes". Beyond this theorical refference, this study proposes the creation of a sixth flux of assets and commodities. In a theorical approach, the fluxes of assets and commodities is analised, so as to investigate its relation with other Appadurei's fluxes. Due to the analysis made, it was possible to confirm that these fluxes bring precious evidence to other cultural studies and is, therefore, of a great value to the researches about the colonial time or about the area